THE INFLUENCE OF E-COMMERCE ADVERTISING PROMOTIONS AND HEDONIC SHOPING VALUE ON IMPULSE BUYING THROUGH CUSTOMER SATISFACTION IN AN ISLAMIC ECONOMIC PERSPECTIVE IN WEST SURABAYA - Fitryani Fitryani; Umu Mardiyanah (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
The research examines and analyzes the influence of E-commerce advertising promos and hedonic shopping value on impulse buying through customer satisfaction from an Islamic economics perspective. Analysis using statistics with the SmartPLS Version 3.0 tool. Research Results of E-commerce Advertising Promotion Variables, Hedonic Shopping Value directly influence Customer Satisfaction from an Islamic economics perspective. The Customer Satisfaction variable directly has a significant effect on Impulse Buying. E-commerce Advertising Promo Variables with Impulse Buying through Customer Satisfaction. The Hedonic Shopping Value variable indirectly has a significant effect on Impulse Buying through Customer Satisfaction. The Hedonic Shopping Value variable and Impulse Buying indirectly has a significant effect through Customer Satisfaction.